AlCoCrFeNi high entropy alloy reinforced Cu-based composite with high strength and ductility after hot extrusion. (February 2021) - Liu, Yunzi; Chen, Jian; Li, Zhao; Wang, Xianhui; Zhang, Peng; Liu, Jiangnan
Abstract: To improve the effectiveness of high entropy alloys (HEAs) as reinforcing agents in metal matrix composites, the 10 vol.% HEA/Cu composite was fabricated by spark plasma sintering, followed by different holding time at 850 °C and hot extrusion. The as-extruded composites were examined by microstructural characterization using scanning electron microscopy, electron probe microanalysis and transmission electron microscopy along with performance tests. The results show that the preheating at 850 °C promotes the diffusion of Al, Co, Cr Fe and Ni from the reinforcement to Cu matrix, along with the diffusion of Cu towards reinforcement, which give rise to the formation of core-shell structure at less than 6 h. However, such core-shell structure is invisible once the preheating time is above 6 h. At less than 6 h, the increased yield strength of the HEA/Cu composite can be ascribed to the solid solution strengthening of Cu matrix stemmed from element diffusion, whereas the improved plasticity is due to the increasing shell thickness in reinforcements with the preheating time. At above 6 h, the strengthening effect of reinforcements decreases significantly, giving rise to the decrease in the yield strength and the improvement in the plasticity. Highlights: AlCoCrFeNi/Cu matrix composite was fabricated by SPS and hot extrusion. At preheating time of less than 6 h, the core-shell of reinforcement in-situ forms. At 6 h and 8 h preheating time, the reinforcement consists of two kinds of FCC phases. In-situ formation of core-shell improves the mechanical property of composites.